1998
DOI: 10.1097/00006842-199811000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptomatology and Vital Exhaustion Are Differentially Related to Behavioral Risk Factors for Coronary Artery Disease

Abstract: Vital exhaustion and depressive symptomatology are differentially associated with relevant external criteria. Vital exhaustion is associated with perceived cardiovascular complaints and history of cardiovascular treatment, whereas depressive symptomatology seems to be more closely connected to disabilities and complaints related to alcohol, drug, and congenital-disorder, and to dysfunctional cognitions and hostility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
131
1
6

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(144 citation statements)
references
References 16 publications
6
131
1
6
Order By: Relevance
“…This then leads to the intriguing question Á is vital exhaustion a marker for lack of positive affect (or vice versa)? Studies assessing an association between vital exhaustion and depression have shown that the constructs are highly correlated (Kopp, Falger, Appels, & Szedmak, 1998;McGowan et al, 2004;Wojciechowski, Strik, Falger, Lousberg, & Honig, 2000). However, it is unclear whether research in this area measures overlapping symptoms of depression and vital exhaustion, or whether the unique symptoms of exhaustion are more important.…”
Section: Vital Exhaustionmentioning
confidence: 99%
“…This then leads to the intriguing question Á is vital exhaustion a marker for lack of positive affect (or vice versa)? Studies assessing an association between vital exhaustion and depression have shown that the constructs are highly correlated (Kopp, Falger, Appels, & Szedmak, 1998;McGowan et al, 2004;Wojciechowski, Strik, Falger, Lousberg, & Honig, 2000). However, it is unclear whether research in this area measures overlapping symptoms of depression and vital exhaustion, or whether the unique symptoms of exhaustion are more important.…”
Section: Vital Exhaustionmentioning
confidence: 99%
“…az alacsonyabb jövedelmû és iskolai végzettségû, magányosan vagy re latíve elszigetelten élõ betegek körében a súlyos depresszióban szenvedõk aránya is jóval magasabb. az életkorból, a nembõl és a szocioökonómiai státuszból fakadó hátrányok erõsíthetik a klinikai depresszió esélyét, és ez rontja a kardiológiai rehabilitáció hatékonyságát is (Berry & Walsh, 2001;Kopp, Falger, appels, & szedmak, 1998). …”
Section: A Kardiológia Betegségek Az Európai Unióban éS Magyarországonunclassified
“…The assessment of VE can be made with the 21-item Maastricht Questionnaire (Appels, Hoppener et al 1987) and, although there is an overlap between VE and depressive symptoms, there is evidence these are distinct conditions (Kopp, Falger et al 1998). …”
Section: Vital Exhaustionmentioning
confidence: 99%